Learners’ Characteristics and Academic Performance: A Study of Kwame Nkrumah University of Science and Technology Primary School, Ghana - Olivia Akrofi (Journal of Education and Learning Technology, 2020)
The learner has a significant role to play in improving his/her academic performance. This study investigated learners’ characteristics contributing to low academic performance in primary school. The study focused on the Kwame Nkrumah University of Science and Technology Primary School in Kumasi, Ghana. Using a qualitative approach, one hundred and twenty (120) learners, sixty (60) parents and thirty-five (35) teachers were purposively sampled using questionnaires, interviews and informal discussions respectively. Responses of learners revealed that some of them felt rejected by peers, did not understand lessons taught, while some were inattentive and attention seekers who tend to disrupt the concentration of studious learners. The findings showed that lack of parental motivation and assistance negatively impact the academic work of learners. The study recommends that a guidance and counselling unit be set up in schools to assist learners develop attitudes and habits for academic achievements..